Strategi Pemenuhan Kompetensi Dasar Perawat dengan Metode Preseptorship: A Systematic Review - Yunita, Satri; Engeltrudis Bunga, Sr (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The need for effective clinical learning to support the transition of newly graduated nurses and nursing students into the clinical environment necessitates the implementation of structured and supportive methods. Preceptorship, which involves experienced nurses serving as mentors, is a strategic approach to bridging competency gaps and has been proven to significantly enhance nurses’ confidence, skills, and clinical knowledge. This study aims to examine strategies for fulfilling nurses’ basic competencies through the preceptorship method. A systematic review was conducted following the PRISMA guidelines and utilizing Zotero software. Articles were retrieved using the PICO strategy from electronic databases including PubMed, ProQuest, and Google Scholar, using relevant keywords. Out of 2,353 articles identified (PubMed: 129, Google Scholar: 1,030, ProQuest: 1,194), 413 duplicate articles were removed. After screening based on title and publication year, 978 articles remained; however, most were either inaccessible in full text or not relevant. As a result, only seven articles met the study criteria and were further critically analyzed. The findings indicate that preceptorship and mentorship methods play a crucial role in enhancing preceptors’ capacity to provide clinical learning. Structured preceptorship fosters a harmonious work environment and supports the development of nurses’ clinical authority according to their placement. Further research is needed to examine the specific effectiveness of preceptorship and mentorship methods in improving nurses’ competencies in clinical practice.